Structural basis of RIP2 activation and signaling - Gong, Qin (2019)
Signals arising from bacterial infections are detected by pathogen recognition receptors (PRRs) and are transduced by specialized adapter proteins in mammalian cells. The Receptor-interacting-serine/threonine-protein kinase 2 (RIPK2 or RIP2) is such an adapter protein that is critical for signal propagation of the Nucleotide-binding-oligomerization-domain-containing proteins 1/2 (NOD1 and NOD2). Dysregulation of this signaling pathway leads to defects in bacterial detection and in some cases autoimmune diseases. Here, we show that the Caspase-activation-and-recruitment-domain (CARD) of RIP2 (RIP2-CARD) forms oligomeric structures upon stimulation by either NOD1-CARD or NOD2-2CARD. We reconstitute this complex, termed the RIPosome in vitro and solve the cryo-EM filament structure of the active RIP2-CARD complex at 4.1 Å resolution. The structure suggests potential mechanisms by which CARD domains from NOD1 and NOD2 initiate the oligomerization process of RIP2-CARD. Together with structure guided mutagenesis experiments at the CARD-CARD interfaces, we demonstrate molecular mechanisms how RIP2 is activated and self-propagating such signal.